Do timber plantations contribute to forest conservation? - Pirard, R.; Dal Secco, L.; Warman, R. (Elsevier, 2016)
For some time there has been a proposition in forestry and nature conservation disciplines that timber plantations can potentially support natural forest conservation outcomes when wood logged in extensive natural forests is substituted by wood production from smaller areas of intensive timber plantations. Here, we have called this the plantation conservation benefit. We review evidence from the literature of this intuitively appealing proposition, both empirical and theoretical, and add emphasis on methods (theoretical modelling, econometrics and descriptive statistics) in order to explicitly address causative mechanisms and potential negative or positive feedback processes. This understanding is critical to developing effective policy. We find a convergence of conclusions of reduced degradation of natural forests associated with the expansion of timber plantations, but also potential increased deforestation due to either lower market value of natural forests in the absence of logging, or displacement effects. Yet, a main limitation of studies is the lack of consideration of the role of policies and institutions beyond market drivers, especially in econometric studies. We conclude on the need for integrated policy approaches applied simultaneously to both natural forests and plantations to maximize the potential benefit.